2016
DOI: 10.1371/journal.pone.0166499
|View full text |Cite
|
Sign up to set email alerts
|

VMP1 Establishes ER-Microdomains that Regulate Membrane Contact Sites and Autophagy

Abstract: The endoplasmic reticulum (ER) regulates organelle dynamics through the formation of membrane contact sites (MCS). Here we describe that VMP1, a multispanning ER-resident protein involved in autophagy, is enriched in ER micro-domains that are in close proximity to diverse organelles in HeLa and Cos-7 cells. These VMP1 puncta are highly dynamic, moving in concert with lipid droplets, mitochondria and endosomes. Some of these micro-domains are associated with ER sliding events and also with fission events of mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 44 publications
12
92
0
Order By: Relevance
“…The tethering function of E-Syt2 and 3 (namely the C2C domain) was required for the proper autophagosome biogenesis on contact sites. Interestingly, VMP1 protein was recently shown to participate in a certain number of ER-driven contact sites (Tábara & Escalante, 2016). Interestingly, VMP1 protein was recently shown to participate in a certain number of ER-driven contact sites (Tábara & Escalante, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The tethering function of E-Syt2 and 3 (namely the C2C domain) was required for the proper autophagosome biogenesis on contact sites. Interestingly, VMP1 protein was recently shown to participate in a certain number of ER-driven contact sites (Tábara & Escalante, 2016). Interestingly, VMP1 protein was recently shown to participate in a certain number of ER-driven contact sites (Tábara & Escalante, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that overexpression of TMEM41B does not perturb its intracellular localization, we tagged the endogenous TMEM41B locus with a C-terminal Myc epitope by CRISPR and validated the knock-in (KI) by immunoblot and genomic PCR (Fig 5B-D). Furthermore, VMP1 KO cells have also been shown to accumulate electron-dense structures, believed to be immature autophagosomes [34,35]. TMEM41B has a predicted "SNARE-associated Golgi protein" domain, which shares homology to bacterial DedA proteins [30], yeast TVP38, and mammalian TMEM41A, TMEM64, and VMP1 (IPR032816, [31]).…”
mentioning
confidence: 99%
“…Vacuole membrane protein 1 (VMP1) is an ER‐resident multispanning protein first identified for its role in autophagy . Recently, we proposed a more general role for VMP1 in regulating MCSs . We found that VMP1 forms ER microdomains in close contact with other organelles such as mitochondria, peroxisomes, lipid droplets, autophagosomes and endosomes.…”
Section: Introductionmentioning
confidence: 94%
“…We found that VMP1 forms ER microdomains in close contact with other organelles such as mitochondria, peroxisomes, lipid droplets, autophagosomes and endosomes. The lack of VMP1 leads to aberrant mitochondrial morphology and larger contact sites between ER and mitochondria, as well as defects in lipid droplets distribution and a blockade in autophagic flux . We hypothesized that VMP1 regulates the size and/or the function of multiple MCSs, but further studies were needed to characterize the nature and properties of these VMP1‐enriched ER subdomains.…”
Section: Introductionmentioning
confidence: 99%